2021
DOI: 10.1093/bioinformatics/btab706
|View full text |Cite
|
Sign up to set email alerts
|

SMILE: mutual information learning for integration of single-cell omics data

Abstract: Motivation Deep learning approaches have empowered single-cell omics data analysis in many ways and generated new insights from complex cellular systems. As there is an increasing need for single cell omics data to be integrated across sources, types, and features of data, the challenges of integrating single-cell omics data are rising. Here, we present an unsupervised deep learning algorithm that learns discriminative representations for single-cell data via maximizing mutual information, SM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Instead of calculating NCE directly on z , we further reduced z to 32-dimension output with linear transformation and 25-dimension SoftMax activated output, through two separated one-layer MLPs. This practice is the same as our previous study, in which we demonstrated an effective approach to learn discriminative representation for single-cell data 22 . Once model training is done, we use encoder E to project both modalities into the joint representation for downstream analyses (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Instead of calculating NCE directly on z , we further reduced z to 32-dimension output with linear transformation and 25-dimension SoftMax activated output, through two separated one-layer MLPs. This practice is the same as our previous study, in which we demonstrated an effective approach to learn discriminative representation for single-cell data 22 . Once model training is done, we use encoder E to project both modalities into the joint representation for downstream analyses (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…We term our method sciCAN (single-cell chromatin accessibility and gene expression data i ntegration via Cycle-consistent Adversarial Network), which removes modality differences while keeping true biological variation. We previously developed a deep learning method, SMILE, to perform integration of multimodal single-cell data 22 . SMILE requires cell anchors for integration.…”
Section: Introductionmentioning
confidence: 99%
“…#9 pipeline is a combination process of #2 and #8 pipelines. Deep-learning-based batch correction methods demonstrated a considerable success to integrative analysis of scRNA-seq data, and we noticed that the frequent practice across these methods is use of batch normalization layer and non-linear activation layer, which splits the whole dataset into multiple mini-batches, standardizes cells in each batch, and transforms the outcome with a non-linear activation function 2,4,5,13,14 . This batch normalization and non-linear activation process do not require weight training, and we included it into the #10 pipeline.…”
Section: Resultsmentioning
confidence: 99%
“…Single cell technology is becoming every day more used to investigate complex questions. Thus, it is becoming important to integrate the results of multiple experiments [ 18 , 20 , 21 ]. Seurat-based integration [ 18 ] is an approach frequently used to aggregate different single cells or different modalities of the same experiment.…”
Section: Resultsmentioning
confidence: 99%